2012
DOI: 10.1016/j.neuro.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to 50 ppb sodium arsenate induces hypothalamic-pituitary-adrenal axis dysregulation in male C57BL/6 mice

Abstract: Over the past two decades, key advancements have been made in understanding the complex pathology that occurs following not only high levels of arsenic exposure (>1ppm) but also levels previously considered to be low (<100 ppb). Past studies have characterized the deleterious effects of arsenic on the various functions of cardiovascular, pulmonary, immunological, respiratory, endocrine and neurological systems. Other research has demonstrated an elevated risk of a multitude of cancers and increased rates of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 53 publications
2
30
1
Order By: Relevance
“…We have previously demonstrated that arsenic-exposed mice fail to activate a normal corticosterone (CORT) response to TMT (Goggin et al, 2012); to determine if fluoxetine attenuates this effect, CORT levels at baseline and after TMT exposure were determined in all animals. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that arsenic-exposed mice fail to activate a normal corticosterone (CORT) response to TMT (Goggin et al, 2012); to determine if fluoxetine attenuates this effect, CORT levels at baseline and after TMT exposure were determined in all animals. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, HPA axis stress responses in the dentate gyrus are mediated in part through the glucocorticoid receptor (GR) and can impact gene expression (de Kloet et al, 2005). For its part, arsenic exposure induces deficits in mRNA expression of neurogenesis-related genes, including Nrc31 (gene for GR protein), Creb1 , and Hdac2 (Goggin et al, 2012; Tyler and Allan, 2013), though the mechanism by which this damage occurs is unclear. Thus to determine the pathways involved in fluoxetine’s neurogenic actions and in arsenic-induced morphological damage, we assessed expression of proteins involved in AHN, including the GR, CREB, HDAC2, and BDNF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These mechanisms, identified in experimental animal studies, include oxidative stress and the production of free radicals resulting in neuronal apoptosis [12,13], impaired hippocampal neurogenesis [14], dysregulation of the hypothalamo-pituitary-adrenal axis including reduced levels of corticosterone receptors in the hippocampus [15,16], epigenetic effects such as reduced DNA methylation in the hippocampus and frontal cortex [17], reductions in brain levels of biogenic amines and other neurotransmitters [18][19][20][21], changes in the expression of the NMDA receptor complex [22], inhibition of neurite outgrowth [23], structural malformation of white matter (e.g., myelin sheaths) [24] and of hippocampal mossy fibers [25], and endocrine disruption, including down-regulation of thyroid hormone receptor genes [26,27].…”
Section: Introductionmentioning
confidence: 99%